Strategies and training programs for the reigning champions in LKS competition - Kurniawan, Sandi; Perianto, Agus (Faculty of Technological and Vocational Education-Universitas Pendidikan Indonesia, 2023)
The Student Competency Competition (LKS) is an annual the Director of Vocational School Development (DITPSMK) agenda that aims to get the best students from each region to compete nationally and represent Indonesia globally. Becoming the defending champion in the LKS competition takes work, and many factors determine the contestants' success. One factor that determines the defending champion's success in the LKS competition is the strategy and training program used in competing. Strategies and training programs are designed to prepare and ensure LKS participants are ready to participate in competitions and become champions. This research focuses on finding and presenting data on strategies and training programs for defending champions in LKS competitions. This study used a qualitative approach with descriptive research, and the research informants were contestants and supervisors who succeeded in becoming the defending champions in the LKS competition. Data collection using interviews, observation, and documentation was expected to answer the research focus. The results of the research found that the strategies carried out by the defending champions in the LKS competition were divided into four crucial components: school, family, stakeholder, and financial components. The management system and collaboration between the four components is the key to the success of the defending champion in the competition. The training programs include spiritual, physical, knowledge, and skills training. The training program is designed and supervised by supervisors and all productive teachers in the school. The synergy between strategy and training programs is the key to the success of the defending champion in LKS in competing.